(untitled) (Research, Society and Development, 2021)
In animal production, the search for alternative, low cost food sources to compose the diets has been constant. Sweet potato is a crop that generates by products with good nutritional values, an example is the branch, which can be included in animal feed, mainly in the form of silage. The ensilage process is one of the main alternatives for food preservation, aiming to meet the demand for forage in the most critical periods. In this context, the use of agricultural residues can be an interesting strategy in certain regions. The aim of this literature review was to evaluate the fermentative and chemical characteristics of sweet potato branch silage. In general, it is observed that sweet potato branch have potential for forage use in ruminant nutrition, especially if preserved in the form of silage, provided that the dry matter content is adjusted. In addition, corn meal has been shown to be efficient to be used as a physical additive in the sweet potato branch ensilage process. Furthermore, the storage period is very important since there is evidence that changes in the nutritional values of ensiled forages occur during the conservation period.